Proposal of Model for Effective Management of Cooperation Activities in Slovak Companies - Vodak, Josef; Soviar, Jakub; Lendel, Viliam; Varmus, Michal (Communications - Scientific letters of the University of Zilina, 2015)
Aim of this article is to offer a proposal for effective planning and organization of cooperation activities in a company, based on a comprehensive analysis of scientific literature and performed empirical research in Slovak republic. The article thus provides a tool for company managers for managing their cooperation activities. Use of this tool is meant to help minimize occurrence of conflict situations and to support smooth progress of cooperation activities from the organizational and planning perspective.